Leverage Sebagai Pemoderasi Pada Transfer Pricing Yang Dipengaruhi Tax Minimiziation, Bonus Mechanism , dan Tunneling Incentive - Mei Dewi Lutfia; Sukirman Sukirman (Universitas Katolik Soegijapranata Semarang, 2021)
The purpose of this study is to analyze the effect of tax minimization, bonus mechanism, and tunneling incentive on transfer pricing with leverage as a moderating variable. The population of this study are mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The sample selection uses a purposive side technique. Samples that meet the criteria are 18 companies with 54 units of analysis, there are 8 outlier so that the number of samples is 46 units of analysis. The data analysis technique is Moderated Regression Analysis (MRA) with IBM SPSS Statistics Version 24 software. This study shows a negative effect of tax minimization, a positive effect of tunneling incentive, and no bonus mechanism effect on transfer pricing decisions. Leverage does not moderate the effect of tax minimization and bonus mechanism on transfer pricing decisions and only significantly moderates the effect of tunneling incentives on transfer pricing decisions.